Vertebroplasty: What Is Important and What Is Not - Al-Ali, F.; Barrow, T.; Luke, K. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: It is important to try to clarify the methodology of vertebroplasty such as amount of cement needed, how many needles to use and the significance of cement extravasation. This prospective study evaluated the potential of vertebroplasty to increase the likelihood of an adjacent vertebral compression fracture (VCF) 1 year or less after vertebroplasty, the correlation between the cement volumes injected and pain relief, and the consequences of cement extravasation. MATERIALS AND METHODS: Pain relief and the incidence of a subsequent fracture of adjacent vertebrae 1 year or less after vertebroplasty were evaluated in 357 patients (660 vertebrae) of mean age 77.5 years with osteoporotic VCFs. The correlation between cement volume and pain relief was assessed with a Pearson correlation coefficient; factors potentially predictive of subsequent adjacent VCFs were explored by multiple logistic regression analysis. RESULTS: Refracture of any vertebrae (adjacent or nonadjacent to the primary fracture) occurred in 18% of the patients 1 year or less after vertebroplasty. Refracture of adjacent vertebrae occurred 1 year or less after vertebroplasty in 12% of the patients. Neither cement volume nor extravasation of cement into the intravertebral disk was a significant predictor of adjacent VCFs. No correlation was found between cement volume and pain relief (r = −0.029). Extravasation of cement into the veins, soft tissue, or disk was observed in 33% of all of the treated VCFs and resulted in no complications. CONCLUSIONS: The incidence of an adjacent VCF 1 year or less after vertebroplasty was comparable with that expected for untreated osteoporotic VCFs. Neither the volume of cement injected nor extravasation of cement into the intravertebral disk affected the likelihood of subsequent adjacent VCFs. Cement volume did not correlate with pain relief.